2020
DOI: 10.4103/ija.ija_697_20
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic: Psychological impact on anaesthesiologists

Abstract: Background and Aim: The anaesthesiologists are at the highest risk of contracting infection of coronavirus disease 2019 (COVID-19) in emergency room, operation theatres and intensive care units. This overwhelming situation can make them prone for psychological stress leading to anxiety and insomnia. MATERIALS AND METHODS We did an online self-administered questionnaire-based observational cross-sectional study amongst anaesthesiologists across India. The objectives were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 29 publications
0
50
0
Order By: Relevance
“…In a study during the H1N1 outbreak, hospital staff who were in their 20's had greater anxiety about becoming infected than did older staff ( 103 ). During COVID-19, HCW who were younger were more likely to experience higher levels of post-traumatic stress symptoms, depression, anxiety, and acute stress compared to older HCW ( 23 , 26 28 , 30 , 32 , 42 , 49 , 54 , 55 , 57 , 61 , 65 , 71 , 75 , 78 , 89 , 90 , 117 , 118 , 121 , 123 , 127 , 131 , 149 , 153 , 154 ). In contrast, eight studies conducted during COVID found that HCW who were older were at greater risk of experiencing higher levels of psychological distress ( 40 , 66 , 86 , 95 , 102 , 114 , 122 , 132 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a study during the H1N1 outbreak, hospital staff who were in their 20's had greater anxiety about becoming infected than did older staff ( 103 ). During COVID-19, HCW who were younger were more likely to experience higher levels of post-traumatic stress symptoms, depression, anxiety, and acute stress compared to older HCW ( 23 , 26 28 , 30 , 32 , 42 , 49 , 54 , 55 , 57 , 61 , 65 , 71 , 75 , 78 , 89 , 90 , 117 , 118 , 121 , 123 , 127 , 131 , 149 , 153 , 154 ). In contrast, eight studies conducted during COVID found that HCW who were older were at greater risk of experiencing higher levels of psychological distress ( 40 , 66 , 86 , 95 , 102 , 114 , 122 , 132 ).…”
Section: Resultsmentioning
confidence: 99%
“…Sixty-one studies reported on fear related to an infectious disease outbreak [ 29 – 31 , 35 37 , 43 , 46 , 53 , 55 , 61 , 64 , 72 , 74 , 78 83 , 85 – 87 , 94 , 95 , 99 , 100 , 107 – 109 , 115 , 117 , 119 , 123 , 128 , 131 , 132 , 134 , 142 , 146 , 147 , 155 – 173 ]. Most of the studies ( n = 52) reported physician’s fear of infecting themselves or their family.…”
Section: Resultsmentioning
confidence: 99%
“…One hundred studies reported on factors associated with psychological symptoms during infectious disease outbreaks. Female sex (compared to male) was the factor most commonly associated with worse psychological symptoms in physicians [ 30 , 41 , 44 , 48 , 63 , 66 , 71 , 77 , 89 , 98 , 112 , 122 , 127 , 128 , 138 , 142 , 144 , 148 , 163 , 165 , 170 , 174 – 189 ]. Other factors associated with poorer psychological outcomes included direct patient contact [ 28 , 32 , 34 , 44 , 46 , 53 , 59 , 64 , 71 , 81 , 95 , 98 , 112 , 122 , 130 , 163 , 169 , 175 , 182 , 183 , 186 , 190 – 192 ] [ 30 , 34 , 41 , 44 , 48 , 59 , 63 , 66 , 71 , 77 , 89 ], single marital status (compared to married) [ 39 , 44 , 59 , 63 , 98 , 122 ], younger age [ 33 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be attributed to increased personal and professional commitments in this time of various new-normal changes in the COVID-19 pandemic. [ 9 ]…”
Section: Discussionmentioning
confidence: 99%